AKTUALISASI PELAYANAN PENDIDIKAN MELALUI BUDAYALITERASI PAGI DI SMPN 1 LATAMBAGA (BEST PRACTICE) - Dakir Torang (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
To realize the objectives of National Education in its entirety, the government has issued Permendikbud No. 23 of 2015 concerning the Development of Ethical Characteristics which contains a structured and planned learning activity realized through the School Literacy Movement (GLS). The Permendikbud is an effort to foster students' character that aims to have students have a culture of reading and writing so as to create a learning culture that can last a lifetime. GLS activities have been carried out since 2015 at SMP Negeri 1 Latambaga. The stages of GLS conducted at SMP Negeri 1 Latambaga include: 1) the stages of understanding; 2) the stage of habituation; 3) stages of learning. To support the implementation of the School Literacy Movement activities several efforts were made at Latambaga 1 Public Middle School, including: 1) Making an expression stage; and 2) Installation of internet networks to facilitate the procurement of wifi in the online learning process. The real impact felt by the existence of the School Literacy Movement is that it can improve students' insights and knowledge, increase vocabulary, improve memory quality, practice skills for thinking and analyzing, increase focus and concentration, can help prevent cognitive decline, can increase one's empathy , and can help students connect with the outside world as a manifestation of the vision of a local school with global culture.